RTF2 controls replication repriming and ribonucleotide excision at the replisome - Brooke A. Conti; Penelope D. Ruiz; Cayla Broton; Nicolas J. Blobel; Molly C. Kottemann; Sunandini Sridhar; Francis P. Lach; Tom F. Wiley; Nanda K. Sasi; Thomas Carroll; Agata Smogorzewska (Nature Communications, 2024)
Abstract DNA replication through a challenging genomic landscape is coordinated by the replisome, which must adjust to local conditions to provide appropriate replication speed and respond to lesions that hinder its progression. We have previously shown that proteasome shuttle proteins, DNA Damage Inducible 1 and 2 (DDI1/2), regulate Replication Termination Factor 2 (RTF2) levels at stalled replisomes, allowing fork stabilization and restart. Here, we show that during unperturbed replication, RTF2 regulates replisome localization of RNase H2, a heterotrimeric enzyme that removes RNA from RNA-DNA heteroduplexes. RTF2, like RNase H2, is essential for mammalian development and maintains normal replication speed. However, persistent RTF2 and RNase H2 at stalled replication forks prevent efficient replication restart, which is dependent on PRIM1, the primase component of DNA polymerase α-primase. Our data show a fundamental need for RTF2-dependent regulation of replication-coupled ribonucleotide removal and reveal the existence of PRIM1-mediated direct replication restart in mammalian cells.